APLIKASI SURAT DESA PULAU KEMANG BERBASIS WEB - Andi lala; Nopa Adiansyah; Monsyah Juansen; Gunawan (JUKOMIKA (Jurnal Ilmu Komputer dan Informatika), 2024)
Pulau Kemang Village is one of the villages located in Ulu Musi District, Empat Lawang Regency. One of the things that is often a problem in the community of Pulau Kemang Village is that making letters in the Village takes a long time because it is manual using Ms.Word and some still use bookkeeping. With these problems, a solution is needed to be able to convert the function of making letters which is still done manually by utilizing information technology, namely by making web-based letters. It is hoped that this new system can increase the efficiency and effectiveness of administration, especially village letters. From these problems, the focus of this study is to increase the efficiency of letter services with a web-based application that uses the method of implementing literature studies, observations, interviews, and type development with the waterfall method and creating a system using the PHP and MySQL programming languages ​​based on the system framework created. At the system testing stage using Beta. Beta testing is a test carried out by several website users, this will be an important step in finding out whether it is in accordance with what the researcher expects.